Match activity profile and heart rate responses of top-level soccer referees during Brazilian national first and second division and regional championships - da Silva, J. F.; Teixeira, A. S.; de Carvalho, J.; Salvador, P. D. N.; Castagna, C.; Venture, A. P.; de Sousa Neto Segundo, J. F.; Guglielmo, L. G. A.; de Lucas, R. D. (Science and Medicine in Football, 2023)
This study aimed to examine the differences in physical match activities and heart rate (HR) responses experienced by Brazilian field referees (FRs) and assistant referees (ARs) during official matches from Serie A, Serie B and Regional championships. The sample was composed of 51 FRs and 87 ARs. Match activities derived from Global Position System and HR response were collected during official matches. FRs and ARs covered higher distances at high-intensity running (HIR; d = 1.17 and 2.53, p < 0.001), sprinting (d = 0.82 and 0.48, p < 0.005) and high-intensity activities (HIA; d = 1.07 and 1.97, p < 0.001) in Serie A and Serie B than in Regional. Changes in the distances covered at HIR (0.80 < d < 3.25, p < 0.005), sprinting (d = 0.42, p = 0.050) and HIA (0.93 < d < 3.01, p < 0.005) between half-matches were observed during Serie A and Serie B. The average %HRmax was progressively increased in both half-matches (0.85 < d < 3.54, p < 0.001) during all championships. For FRs, Serie A and Regional elicited the highest average %HRmax (0.80 3C d < 1.37, p < 0.030). For ARs, Serie A and Serie B elicited the highest average %HRmax (2.14 < d< 3.87, p < 0.001). In conclusion, the physical match activities and average %HRmax of Brazilian FRs and ARs differ across championship levels. FRs and ARs acting in Regional championships are likely to need specific preparation to support the higher physical demand observed at higher competition levels.